M Moderasi Beragama antara Islam dan Tionghoa di Pulau Bangka: Religious Moderation Between Islam and Tionghoa in Bangka Island - Irawan; Nasrun (Direktorat Jenderal Bimbingan Masyarakat Islam, 2024)
Abstract: This article aims to explain the religious moderation between Islam and Tionghoa in Bangka Island. This article is categorized as field research and analyzed using descriptive qualitative method. The approach used in this article is a historical sociological approach. In analyzing the research results, Milton M. Gordon's theory: multi-stages of assimilation and Peter L. Berger's theory: the sacred canopy are used. This article concludes that Islamic moderation between Islam and Tionghoa in Bangka is going well. This is due to history, assimilation (structural assimilation, cultural assimilation, and receptive assimilation), externalization, objectivation, and internalization. Keywords: Islam, Tionghoa, religious moderation.